2021
DOI: 10.3389/fpls.2021.621954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grafting on Viral Resistance of Non-transgenic Plum Scion Combined With Transgenic PPV-Resistant Rootstock

Abstract: In stone fruit trees, resistance to Plum pox virus (PPV) can be achieved through the specific degradation of viral RNA by the mechanism of RNA interference (RNAi). Transgenic virus-resistant plants, however, raise serious biosafety concerns due to the insertion and expression of hairpin constructs that usually contain various selective foreign genes. Since a mature stone tree represents a combination of scion and rootstock, grafting commercial varieties onto transgenic virus-tolerant rootstocks is a possible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
1
16
1
Order By: Relevance
“…They found that transgenic rootstocks remained virus free but could not protect the scion due to the lack of an efficient transfer of transgene-derived siRNAs from the rootstocks to the scions. However, scions accumulated specific endogen sRNAs characteristic of the rootstocks (Sidorova et al , 2021). Conversely, Zhao and Song, (2014) showed that PNRSV-hpRNA-derived siRNAs were transmitted up to 1.2 m from the transgenic sweet cherry rootstocks to the non-transgenic scions conferring enhanced PNRSV resistance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They found that transgenic rootstocks remained virus free but could not protect the scion due to the lack of an efficient transfer of transgene-derived siRNAs from the rootstocks to the scions. However, scions accumulated specific endogen sRNAs characteristic of the rootstocks (Sidorova et al , 2021). Conversely, Zhao and Song, (2014) showed that PNRSV-hpRNA-derived siRNAs were transmitted up to 1.2 m from the transgenic sweet cherry rootstocks to the non-transgenic scions conferring enhanced PNRSV resistance.…”
Section: Discussionmentioning
confidence: 97%
“…However, despite this encouraging evidence, contradictory results were also obtained in herbaceous and woody plants (Leibman et al , 2015;Sidorova et al , 2021). In particular, Sidorova et al , (2021) showed that although the transgenic rootstocks of the interspecific Elita cv. [(Prunus pumila L. × P.…”
Section: Introductionmentioning
confidence: 99%
“…The trans-grafting method comprises the grafting of a non-genetically modified scion onto a genetically altered rootstock. The scion obtains benefits and traits conferred by transgenes in the rootstock, but the end products, such as fruits, do not contain the transgene and hence are not genetically modified [ 112 , 113 ]. Another innovation is micrografting, which involves the in vitro grafting of small shoot apices or lateral buds onto decapitated rootstock seedlings [ 110 , 114 , 115 ].…”
Section: Molecular Toolsmentioning
confidence: 99%
“…The molecular basis of grafting signaling is not fully understood, but recent research suggests that different plant hormones, proteins, epigenetic events, and several types of RNA could be responsible for changes in scion [ 103 , 113 , 115 , 116 , 117 , 118 , 119 , 120 ].…”
Section: Molecular Toolsmentioning
confidence: 99%
“…A recent report showed that even the genomes could transfer horizontally via organelle travel during the remodeling of PD and vascular connection at the root-scion junction ( Hertle et al, 2021 ). Previous reports have successfully used transgenic rootstocks to transfer transgene-mediated traits to the wild-type scion parts- for example, the development of CMV resistance in tomato ( Bai et al, 2016 ), Pierce’s disease resistance in grape ( Dandekar et al, 2019 ), PPV resistance in plum ( Sidorova et al, 2021 ), and increased nitrogen levels in walnut overexpressing an ammonium transporter gene ( Liu et al, 2021 ). In such studies, engineering of PD trafficking and the use of transgene-free CRISPR techniques to attain desired traits would be highly desirable because the non-transgenic genome editing approach may easily avoid the GM issues and related-regulatory hurdles.…”
Section: Genome Editing Toolsmentioning
confidence: 99%